Principled Spying : The Ethics of Secret Intelligence - Omand, David; Phythian, Mark (Book collections on Project MUSE., 2018)
Collecting and analyzing intelligence are essential to national security and an effective foreign policy. The public also looks to its security agencies for protection from terrorism, from serious criminality, and to be safe in using cyberspace. But intelligence activities pose inherent dilemmas for democratic societies. How far should the government be allowed to go in collecting and using intelligence before it jeopardizes the freedoms that citizens hold dear? This is one of the great unresolved issues of public policy, and it sits at the heart of broader debates concerning the relationship between the citizen and the state. In Safe and Sound, national security practitioner David Omand and intelligence scholar Mark Phythian offer an ethical framework for examining these issues and structure the book as an engaging debate. Rather than simply presenting their positions, throughout the book they pose key questions to each other and to the reader and offer contrasting perspectives to stimulate further discussion. They probe key areas of secret intelligence including human intelligence, surveillance, ethics of covert and clandestine actions, and oversight and accountability. The authors disagree on some key questions, but in the course of their debate they demonstrate that it is possible to strike a balance between liberty and security.